2013
DOI: 10.1038/onc.2013.374
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor and microRNA-21 axis downregulates transforming growth factor beta receptor II (TGFBR2) expression in prostate cancer

Abstract: Prostate cancer cells escape growth inhibition from TGFβ by down-regulating TGFβ receptors. However, the mechanism by which cancer cells down-regulate TGFβ receptors in prostate is not clear. Here, we showed that coordinated action of miR-21 and androgen receptor (AR) signaling played a critical role in inhibiting TGFβ receptor II (TGFBR2) expression in prostate cancer cells. Our results revealed that miR-21 suppresses TGFBR2 levels by binding to its 3'UTR and AR signaling further potentiates this effect in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
102
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(108 citation statements)
references
References 41 publications
3
102
1
2
Order By: Relevance
“…In addition, several recent studies showed that AR can indirectly regulate the expression and function of its target gene also via mechanisms involving miRNAs (Ma et al 2013, Lyu et al 2014, Mishra et al 2014, Pasqualini et al 2015. In this study, we found that miR-126* could decrease FSHR expression and increase the rate of apoptosis in pGCs by binding directly to the 3′-UTR of FSHR.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…In addition, several recent studies showed that AR can indirectly regulate the expression and function of its target gene also via mechanisms involving miRNAs (Ma et al 2013, Lyu et al 2014, Mishra et al 2014, Pasqualini et al 2015. In this study, we found that miR-126* could decrease FSHR expression and increase the rate of apoptosis in pGCs by binding directly to the 3′-UTR of FSHR.…”
Section: Discussionsupporting
confidence: 47%
“…One downstream target of AR is miR-125b, which represses p53 expression; this miRNA cooperates with AR to synergistically inhibit the p53 function in mGCs (Sen et al 2014). Similarly, Ribas et al (2009) showed that androgen-bound AR up-regulates expression of miR-21, and the AR/miR-21 axis exerts oncogenic effects in prostate tumors by down-regulating TGFBR2 (Mishra et al 2014). Therefore, we concluded that the coordinated action of AR and miR-126* plays a critical role in inhibiting FSHR expression in pGCs.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the cell viability changes for both miRNAs were similar to the MDM4 siRNA-positive control, we believe the latter scenario is likely. Besides p53, MDM4 interacts with several other proteins including p21, a cyclin-dependent kinase inhibitor whose expression is associated with reduced proliferation in prostate cancer (Jin et al 2008, Lee & Lu 2011, Peng et al 2013, the transcription factor E2F1, which is known to play a role in cell-cycle regulation in prostate cancer (Strachan et al 2003, Lee et al 2013, the E3 ubiquitin ligase MDM2 that also harbours polymorphisms associated with the risk of prostate cancer (Badciong & Haas 2002 and both Smad3 and Smad4, which are major activating components of the transforming growth factor-b (TGF-b) signalling pathway that has been shown to repress growth in prostate cancer (Kadakia et al 2002, Bjerke et al 2014, Mishra et al 2014. As MDM4 probably plays a role in cancer susceptibility and progression via multiple pathways, further study is required to assess the prostatespecific effects of miRNA-mediated MDM4 levels on each of these pathways.…”
Section: Discussionmentioning
confidence: 99%
“…2A). Among these differentially expressed miRNAs, three miRNAs, including miR-21, miR-130b, and miR-92a, caught our attention because these miRNAs have been reported to modulate both differentiation and malignant progression of cancer (25)(26)(27)(28)(29)(30).…”
Section: Sdf-1 Expression Levels Are Upregulated During Malignant Promentioning
confidence: 99%